2003
DOI: 10.1039/b209296d
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of water vapour from humid air in carbon molecular sieves: Carbosieve S-III and Carboxens 569, 1000 and 1001

Abstract: The adsorption of water vapour in carbon molecular sieves (CMS) used to determine volatile organic compounds (VOCs) in air was investigated. The CMS mass in the trap was found not to affect the mass of retained water under conditions of incomplete saturation of the adsorbent bed with water. Thus, the restrictions commonly imposed on the CMS mass are not necessary. The usefulness of four different CMSs to sample large volumes of humid air was estimated. Carboxen 1000 exhibited the best performance. To assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 13 publications
(21 reference statements)
1
14
0
Order By: Relevance
“…The evaluation of a multibed trap without the presence of a CMS showed that some of the main components in breath samples (e.g., acetone, methanol, ethanol) cannot be adequately adsorbed when only graphitized carbons are present in the sorbent tube. Given that Carboxen 1000 saturates at larger volumes of water than other CMS [26], it would seem to be the best choice for the analysis of breath samples.…”
Section: Microtrap Evaluationmentioning
confidence: 99%
“…The evaluation of a multibed trap without the presence of a CMS showed that some of the main components in breath samples (e.g., acetone, methanol, ethanol) cannot be adequately adsorbed when only graphitized carbons are present in the sorbent tube. Given that Carboxen 1000 saturates at larger volumes of water than other CMS [26], it would seem to be the best choice for the analysis of breath samples.…”
Section: Microtrap Evaluationmentioning
confidence: 99%
“…Graphitized carbons do not adsorb water [16 -18] unlike carbon molecular sieves (CMS), which whilst adsorbing high amounts of water are required for the adsorption of highly volatile compounds. Fastyn et al [19] have demonstrated that Carboxen 1000 is the best choice for CMS as it does not become watersaturated with volumes of up to 5 L and 95% relative humidity (RH). In a previous study [6], we evaluated the capacity of a multi-bed sorption trap, containing a CMS (Carboxen 1000) in 100% RH samples, to adsorb VOCs.…”
Section: Introductionmentioning
confidence: 99%
“…Helmig and Vierling [48] proposed that the amount of adsorbed water depends on the volume and relative humidity of air, temperature, and mass (and identity) of the sorbent. Fastyn et al [49] proposed that the magnitude of the CMS mass is restricted by the tube dimensions, especially in the case of multilayer traps, and the hydraulic resistance; hence they recommended the use of Carboxen 1000 as an optional CMS for sampling large volumes of humid air, instead of other comparable materials (e. g., Carbosieve S-III, Carboxen 569, or Carboxen 1001). In contrast, graphitized carbon blacks (GCB), characterized by their high hydrophobicity and low specific surface area without micro-pores, do not adsorb water; they are hence ideal for sampling in an extremely humid atmosphere [45 -46].…”
Section: Gc Analysis 41 Basics For Gc Analysis: Samplingmentioning
confidence: 99%
“…Multibed adsorption tubes can also employ a CMS as the strongest adsorbent in the last layer. However, contact with humid air can deteriorate the sampling efficiency by blocking the adsorbent surface; if this phenomenon occurs, it can lead to as large as a tenfold decrease in safe sampling volume [49]. Helmig and Vierling [48] proposed that the amount of adsorbed water depends on the volume and relative humidity of air, temperature, and mass (and identity) of the sorbent.…”
Section: Gc Analysis 41 Basics For Gc Analysis: Samplingmentioning
confidence: 99%
See 1 more Smart Citation